Teleworking effect on job burnout of higher education administrative personnel in the Junín region, Peru - Almonacid Nieto, Jhuliana Mayly (2020)
This research aims to determine the effect of the adoption of teleworking on the development of job exhaustion of the higher education administrative staff in Junín during the crisis of COVID- 19. The applied and correlational research was carried out with the participation of 300 adminis- trative workers of higher education by applying a questionnaire of 40 questions. The results ob- tained show that having teleworking skills reduces emotional fatigue and depersonalization since the collaborator can self-regulate his behavior when faced with stressors. Likewise, these skills generate a positive effect on personal fulfillment, allowing the teleworker to achieve a satisfactory personal fulfillment of having said skills. On the other hand, telework conditions generate a hidden effect on emotional exhaustion, depersonalization and personal fulfillment; therefore, this dimen- sion does not contribute to the reduction or increase of the mentioned dimensions. The work-life balance dimension does not generate any effect on any of the factors. It is concluded that the development of skills for teleworking is a relevant factor to achieve personal fulfillment in tele- workers, while teleworking conditions do not reduce job burnout.